Trauma osteomuscular características de los pacientes admitidos en un servicio de urgencias de un hospital de tercer nivel, Medellín 1998 (2000)
ABSTRACT: The diagnosis of osteomuscular trauma characterizes a cohort of 616 patients who were cared for in the emergency room of a tertiary care hospital in Medellín in the months of August to December, 1998. The study was performed through an inquiry with data provided by the clinical history, from the actual observation of nursing students and interviews with the patient and his family. The results describe the characteristics of the population, the consumption of psychoactive substances, the aggressor, and the evaluation of the patients, by means of a prognostic scale of trauma score which establishes differences according to the type of fracture. Disability was studied with a scale of functionality. The data alert us of the need to establish rehabilition programs for the patient early, as well as training programs for the nurse. The lethality for persons who presented with open fractures was 21.4% and for closed fractures was 7.4%, values which suggest the need of trauma units in the city.